Altered high density lipoprotein (HDL), triglyceride (TG) and anthropometric measurements in normal, overweight and obese under graduate medical students - Shukla, Ashish; Kaur, Jaskiran; Gupta, Akash (International Journal of Research in Medical Sciences, 2017)
Background:Obesity has reached epidemic proportions inIndia, affecting 5% of the country’s population. Urbanization and modernization has been associated with obesity in population of younger generation. The aim of the study was to find out variation in metabolic indicators (HDL, TG and anthropometric measurements) of normal overweight and obese undergraduate medical students. Methods:Total of 194 students took part in this study. Their height, weight and waist circumference were measured by standard methods. Their serum was estimated for HDL, TG and, fasting sugar on fully automatic Vitros 250 dry chemistry analyser from Orthoclinical diagnostics from Johnson & Johnson USA. Results:Over all females students were more overweight (Females 16% and Males 8%) and obese (F 18%, M 9%) as compared to males. Blood pressure, weight, waist circumference, HDL, and TG levels were more in overweight and obese group as compared to normal group. Conclusion:The results of the current study have shown an increasing trend of obesity and derangement of metabolic indicators among under graduate medical students.